Upaya Orang Tua Dalam Meningkatkan Kemandirian Belajar Anak Usia 4-8 Tahun di Desa Tanjung Lombok Utara - Mahendra, Juandra Prisma; Marzoan, Lalu; Rahayu, Fitriani (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to determine the role of parents in increasing the learning independence of children aged 4-8 years. This research examines the efforts of parents to familiarize their children with independent learning. This research is descriptive qualitative research with data collection techniques in the form of observation, interviews and documentation. To measure the validity of the data, researchers used triangulation techniques, member checks, and peer discussion. The results of this research show that parents' efforts to increase the learning independence of children aged 4-8 years in Tanjung Village include accompanying children when studying at home, controlling children's daily activities, being good role models, and carrying out habituation and discipline.